2001
DOI: 10.2337/diabetes.50.12.2700
|View full text |Cite
|
Sign up to set email alerts
|

Protection From Type 1 Diabetes in the Face of High Levels of Activated Autoaggressive Lymphocytes in a Viral Transgenic Mouse Model Crossed to the SV129 Strain

Abstract: In comparing the incidence of virally induced type 1 diabetes in F 1 crosses of RIP-LCMV mice to three different mouse strains identical at the major histocompatibility complex H-2D b locus, we surprisingly found that disease development was reduced by 80% in F 1 crosses to the SV129 genetic background and by 60% after eight backcrosses to the original C57BL/6 RIP-LCMV mice. In this model, diabetes is strongly dependent on a virally induced H-2D b -restricted cytotoxic T-cell (CTL) response. Importantly, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This experiment was repeated three times and mean values (± SEM) are displayed. *P < 0.05. onic stem cells from knockout lines are known to protect from T1D in RIP-LCMV mice (42). In contrast to RIP-LCMV-NP × K b (+) littermates, RIP-LCMV-NP × K b (-) mice did not have accelerated T1D after secondary PV infection.…”
Section: Sequential Infection With Lcmv and Pv Results In Accumulatiomentioning
confidence: 95%
“…This experiment was repeated three times and mean values (± SEM) are displayed. *P < 0.05. onic stem cells from knockout lines are known to protect from T1D in RIP-LCMV mice (42). In contrast to RIP-LCMV-NP × K b (+) littermates, RIP-LCMV-NP × K b (-) mice did not have accelerated T1D after secondary PV infection.…”
Section: Sequential Infection With Lcmv and Pv Results In Accumulatiomentioning
confidence: 95%
“…In the RIP-LCMV model of autoimmune diabetes, von Herrath et al (46) reported that the ability to resist the development of diabetes differed drastically between the 129 and the C57BL/6 strain, and they speculated that this difference was the result of differences in the abilities of these two strains of mice to regenerate ␤-cells. It has also been reported that partial pancreactectomy enhanced resistance to STZ-induced diabetes (11) and that neonatal rats are able to spontaneously recover from STZ-induced diabetes (47).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of intracellular calcium concentration. Dual-wavelength excitation spectrophotometry was used to measure intracellular calcium concentration ([Ca 2ϩ ] i ) as described previously (46). Briefly, isolated pancreatic islets were loaded with Fura-2 by a 25-min incubation at 37°C in Krebs-Ringer buffer containing 2 mmol/l glucose and 5 mol/l Fura 2-AM (Molecular Probes, Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Sreenan et al (4) have reported increased β-cell proliferation in NOD mice that exhibit infiltration of pancreatic islets prior to the onset of diabetes. In addition, von Herrath et al (5) reported that nondiabetic RIP-LCMV x SV129 mice, where the numbers and effector functions of autoaggressive CD4 + and CD8 + lymphocytes were not decreased, have increased β-cell regeneration compared with nondiabetic C57BL/6 controls. In other studies, Sherry et al (6) suggested the increased β-cell proliferation that occurs after arresting the autoimmune process is secondary to effects of the inflammatory infiltrate.…”
Section: Introductionmentioning
confidence: 99%